2017
DOI: 10.1159/000477672
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Gender on Tumour Stage in In-House Complications and Choice of Urinary Diversion: Results of the Austrian Cystectomy Registry

Abstract: Introduction and Objectives: Bladder cancer is characterized by gender-dependent disparities. To further address this issue, we analysed a prospective, multicentre cystectomy registry. Methods: An online database was developed that included patient demographics, intra/perioperative data, surgical data and in-house complications. Results: Four hundred fifty-eight patients (112 [24.5%] women and 346 [75.5%] men) were analysed. Men and women were comparable regarding age (mean 68 years), body mass index (mean 26.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
4
1
1
Order By: Relevance
“…A somewhat greater age difference between males and females (1 year [3] vs. 3.1 years in this study) and a less favorable stage distribution in females are further demographic differences between the current and the cited study [3]. A similar difference between females and males concerning the presence of extravesical disease (T3-4, 58.7 vs. 47.2% [8]) as in the current study was observed in a recent multicenter study from Austria [7], whereas in a Canadian multicenter study that observed narrowly identical mortality rates lower differences (T3-4 in females 61 vs. 58% in males [6]) were found. In one multicenter study, a lower 90-day mortality rate was observed in females [9], a finding that was not confirmed in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 43%
“…A somewhat greater age difference between males and females (1 year [3] vs. 3.1 years in this study) and a less favorable stage distribution in females are further demographic differences between the current and the cited study [3]. A similar difference between females and males concerning the presence of extravesical disease (T3-4, 58.7 vs. 47.2% [8]) as in the current study was observed in a recent multicenter study from Austria [7], whereas in a Canadian multicenter study that observed narrowly identical mortality rates lower differences (T3-4 in females 61 vs. 58% in males [6]) were found. In one multicenter study, a lower 90-day mortality rate was observed in females [9], a finding that was not confirmed in our study (Table 1).…”
Section: Discussioncontrasting
confidence: 43%
“…The Austrian Cystectomy Registry demonstrated several gender-related differences in patients undergoing RC. The higher transfusion rate, the rare use of orthotopic bladder substitutes and the higher in-house complication rate underline the higher complexity of this procedure in women [17]. …”
Section: Discussionmentioning
confidence: 99%
“…Some single-center analyses have reported that women undergoing RC have longer operative time, more blood loss, and more frequent perioperative complications and a higher 90-day mortality risk. In addition, the rates of pelvic lymph node dissection and continent diversion are lower for women [ 17 , 18 ]. In a recent analysis of a large US RC cohort, female sex was associated with longer operative time and length of stay, while reoperation, readmission and 30-day mortality rates were similar [ 19 ].…”
Section: Introductionmentioning
confidence: 99%